The design and validation of an instrument to measure teachers' professional development at work. Issue 2 (3rd May 2016) - Evers, Arnoud T.; Kreijns, Karel; Van der Heijden, Béatrice I.J.M.
ABSTRACT: After graduation, it is essential for teachers to continue working on their professional development since they need to be prepared for the requirements of tomorrow's knowledge- and technology-based society, a more varied student and pupil population creating new responsibilities, and higher social expectations from schools and the society as a whole. Although attention for teachers' professional development at work is increasing, the availability of valid survey instruments that measure their participation in professional development at work is still limited. Based on a literature review, such an instrument was designed. This 21-item self-report measure, using a 4-point rating scale, makes an inventory of teachers' participation in activities contributing to professional development. The purpose of the instrument is to make teachers, school leaders and other stakeholders aware of whether, and to what degree, teachers engage in learning at work. This is important because ultimately the quality of education depends on it. A survey was administered in 9 Dutch primary schools and 15 Dutch secondary schools. Exploratory and Confirmatory Factor Analysis confirmed a six-factor structure, and augments earlier findings in the field. The reliabilities of the six subscales were sufficient to good.